1994
DOI: 10.1159/000110358
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cognitive Impairment and Associated Factors among Elderly Hong Kong Chinese Aged 70 Years and Over

Abstract: The prevalence of cognitive impairment was determined in a random age- and sex-stratified sample of 2,011 elderly Hong Kong Chinese, aged 70 years and over, consisting of subjects living in the community and in institutions. The Information/ Orientation Section of the Clifton Assessment Procedure was used as the screening instrument using a cutoff point of 7. The overall age-adjusted prevalence was 5% for men and 22% for women, and 15% for both sexes combined. Univariate analysis identified the following assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 23 publications
4
38
0
1
Order By: Relevance
“…Demographic and clinical variables between the participants and patients who were excluded from the study were compared by 2 and Mann-Whitney U tests. To investigate the clinical determinants of PSDE, a univariate logistic regression was first performed to identify possible risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic and clinical variables between the participants and patients who were excluded from the study were compared by 2 and Mann-Whitney U tests. To investigate the clinical determinants of PSDE, a univariate logistic regression was first performed to identify possible risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…1 Stroke significantly contributes to the development of cognitive impairment in stroke sufferers. 2 Stroke is clearly related to vascular dementia, the secondmost-common type of dementia. 3 Stroke increases the risk of dementia up to 12 times.…”
mentioning
confidence: 99%
“…Previous studies have suggested that low education might be a risk factor per se for poststroke dementia [4,6], Alzheimer's disease [5,7], and all types of dementia [3,8,9,10]. However, these proposals are difficult to verify, since a low educational level is associated with impaired performance in cognitive tests [39][40][41][42][43], and with the usual diagnostic criteria, dementia may be detected earlier in subjects with a lower premorbid cognitive level. The results from this study point to another possibility, namely that an increased cardiovascular risk amongst lower-educated persons may contribute to cognitive impairment of vascular origin.…”
Section: Discussionmentioning
confidence: 99%
“…The overall response rate was 60%. Details of the sampling method and of the baseline cohort have been reported elsewhere [13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%